Factors Affecting Mortality in Adult Tetanus Patients - Khrisnan, Lohghinee; Ong, Anam; Panigoro, Ramdan (Althea Medical Journal, 2015)
Background: Tetanus is a devastating disease that is associated with high mortality. The aim of this studyÂ was to analyze the prognostic factors that were associated with high mortality in tetanus.Â Methods: This was an analytical study and the data was collected retrospectively from 1 JanuaryÂ 2010â31October 2012 in the Department of Neurology, Dr. Hasan Sadikin General Hospital.Results: Out of hundred thirty two cases only 87 cases of tetanus patient have complete medical records.Â There were 54 male and 33 female. The age range was 35-49 years old. Mortality rate was high (32.18%).Â The most frequent wound site is extremities (85.07 %). The absence of post-injury tetanus vaccination wasÂ 75.86%, period of onset <48 hours was 67.82% and the use of mechanical ventilation and tracheostomyÂ 36.07%. Mortality was significantly associated with an incubation period <7 days (p<0.05), presence of fever(p <0.05), co morbidity of autonomic storm (p<0.01), and the severity of the disease by grade 5 (p<0.05).Conclusions: Factors affecting the mortality in adult tetanus patients were significant for incubation period,Â fever, co morbidity and severity of the disease by grade. [AMJ.2015;2(1):157â61]